(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2022)
The honorable biography of the Prophet presented the texts of revelation in an applied and practical way, explained by explanation, statement and detail, and by behavior and representation, in every framework and in any field and situation. their biographies; In order for people to feel in that biography the places of emulation and benefit, the biography of the Prophet Muhammad ? is the first to walk by study, and there is no doubt that scholars - ancient and modern - paid attention to the biography of the Prophet ? because with his guidance ? life is straightened and the path becomes clear, and one of the reasons for interest in studying the Prophet’s biography: strengthening faith and certainty in the hearts of Muslims, and that no matter how hard things are against them, and no matter how strong Satan and his soldiers are, they have a good example in the Messenger of God, and they have a practical example among the honorable Companions.